Efeito do tempo de tratamento e da dose de fluoreto administrada cronicamente na expressão proteica em fígado de ratos - Pereira, Heloisa Aparecida Barbosa da Silva (2015)
In a previous study conducted by our group, it was noticed that fluoride (F) can induce changes in the expression of several liver proteins. Reports in the literature suggest that the changes caused by F in the body are dose- and time-dependent. The objective of this study was to analyze the effect of different F concentrations, exposure time to this ion and concomitant exposure to a high calorie diet in the metabolism of lipids and protein expression in the liver of rats. The study was divided into 2 steps. The first step included 72 21-day-old male Wistar rats that were divided into 2 groups (n=36) according to the diet administered (AIN-93M and Presence). Each group was further divided according to the duration of the treatment (20 or 60 days). In addition, each these was divided into 3 subgroups (n=6), according to the concentration of F administrated in the drinking water, as follows: 0 mg/L (control), 15 mg/L or 50 mg/L. After the experimental period, the animals were anesthetized and the liver and blood were collected. F analysis in plasma and liver tissue was done. Part of the liver was fixed for histological analysis. Lipids were analyzed in plasma and triglycerides were analyzed in the liver. Expressions of proteins were evaluated in the liver by Western blotting. In the second step the only Presence diet were use and the groups experimental the same as previously described. At the end of experimental period, liver and plasma were collected. F concentration in plasma and liver were analyzed. Liver proteins were extracted and prepared for mass spectrometry analysis. Proteins were sequenced and identified. The analysis of F concentrations indicated a doseresponse increase in plasma, regardless the time of exposure to F and type of diet. F concentrations in the liver were higher in the groups receiving 50 ppm F in respect to control. Administration of F altered the lipid profile, with a reduction in TGA in plasma and increase in HDL when the hypercaloric diet was used. The expression of GRP78, ERP29 and SOD2 and Apo-E was altered by F, under the influence of time and type of diet administered. For the groups receiving 50 mgF/L, it was observed an increase in the concentration of proteins related to the defense against oxidative stress and ER stress. For the group that received the concentration of 15 mgF/L, changes in structural proteins, mitochondrial proteins and proteins related to cell proliferation were observed, depending on the time of administration. The results suggest an adaptive mechanism of liver upon exposure to F, which seems to be related to the activation of proteins related to maintenance of homeostasis and that fight against oxidative stress and ER stress caused by this ion.